Reliability of Hepatus® for Evaluating Liver Fibrosis in Chronic Hepatitis B - Jessica Cynthia Febryani; Muhammad Begawan Bestari; Haryono -; Dolvy Girawan; Nenny Agustanti; Yudi Wahyudi; Siti Aminah Abdurachman (The Indonesian Society for Digestive Endoscopy, 2022)
Abstract BackgroundAmong non-invasive strategies available for liver fibrosis assessment, transient elastography is widely used, as it is non-invasive and can be repeated. Hepatus® (Mindray, China) is one novel instrument for measuring liver stiffness that is now available in the market with lower price than its precursor, FibroScan® (Echosens, Paris). MethodIn this cross sectional study, CHB patients in single center were recruited consecutively in October 2021-December 2021. The patients were examined for LSM with two transient elastography instruments in one visit. The first instrument was Hepatus® (Mindray, China) and the second one was FibroScan® (Echosens, Paris). Both measurements were done by the same operator. ResultsA total of 68 CHB patients were enrolled in this study. Median score of LSM by Hepatus® and FibroScan® were 7.6 (5.92-11.88) and 7.35 (5.63-11.80) respectively. Spearman rank analysis for correlation showed a significant correlation between the results of the two instruments ( r= 0.8, p 0.05). The number of patients with significant fibrosis (≥8 kPa) identified by Hepatus® and FibroScan® were 28 (41%) and 29 (43%) respectively. McNemar test yielded no significant difference of the results (p= 1.000), and Cohen’s kappa measure of agreement showed moderate agreement (κ = 0.789 and p 0.005). ConclusionHepatus® identified similar number of significant fibrosis patients with FibroScan®, with the results of liver stiffness measurement between the two instruments correlated significantly. Hepatus® has a potential as an alternative tool for measuring liver stiffness with a more economic price. KeywordsHepatus®, FibroScan®, transient elastography, liver fibrosis, CHB